Senegal : Staff Report for the 2018 Article IV Consultation and Seventh Review Under the Policy Support Instrument and Request for Modification of Assessment Criteria--Debt Sustainability Analysis-Press Release; Staff Report; and Statement by the Executive Director for Senegal. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2019)
Senegal's main challenge is sustaining high GDP growth rates while maintaining fiscal sustainability and improving the business environment to create jobs for the fast-growing population. The second phase of the Plan Senegal Emergent (PSE) covering 2019-23 sets out a comprehensive reform agenda to achieve these objectives. Fiscal reforms should aim to increase revenues, strengthen public financial management (PFM), and improve the composition and quality of spending. Structural reforms to facilitate private investment and competitiveness would provide durable sources of growth, while development of a fiscal framework for oil and gas aligned with international best practice would ensure that these natural resources provide high economic and social returns. Further progress on improving the business environment will require simplifying tax administration and reforms to facilitate SME access to finance, and further develop the Special Economic Zones (SEZs). Policies to address gender and inequality issues would contribute to poverty reduction and well-distributed growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet